A study on the influence of spiritual leadership on knowledge sharing behavior within telecommunication industry in Malaysia - Abdul Wahid, Nur Kamariah; Mohd Mustamil, Norizah; Mustaffa, Nur Fariza (GIAP Journals, 2019)
The present study is exploring the outcome of such areas through a combination of both qualitative and quantitative perspective methods, to provide with empirical evidence for the research problem, and also to help answer questions that cannot be answered by qualitative or quantitative approaches alone. The Exploratory Sequential Design as in model development has been selected for this study for no specificity of guiding framework to begin with as it integrates diverse areas within spiritual leadership and knowledge sharing behavior with integration to islamic leadership model, that require to begin with qualitative exploration with the findings of such leadership style able to produce the values within the workplace that ignite the inner-sense among the employees to feel the conscience and compassion to share knowledge beyond conventional motivational factors as in rewards, power, and relationships, aligned to the Islamic leadership model perspective.